Maternal Nutritional Adequacy and Breast Milk Production Among Lactating Mothers in a Rural Primary Health Care Setting in Indonesia - Aguslina Aguslina; Cut Yuniwati; Hendrika Wijaya Kartika Putri (Jurnal Kesehatan Ibu dan Anak, 2026)
Adequate maternal nutrition during lactation is essential for maintaining maternal health and supporting optimal breast milk production. However, evidence regarding the relationship between maternal nutritional adequacy and breast milk production in primary health care settings remains limited, particularly in rural areas of Indonesia. This study aimed to examine the association between maternal nutritional adequacy and breast milk production among lactating mothers in a primary health care setting in North Aceh, Indonesia. A descriptive analytic study with a cross-sectional design was conducted from June to August 2024 among lactating mothers in the catchment area of the Nisam Primary Health Center, North Aceh, Indonesia. Total sampling was employed, and all eligible lactating mothers were included, resulting in a final sample of 41 participants. Maternal nutritional adequacy was assessed as a composite variable encompassing dietary intake, meal patterns, nutritional knowledge, and socioeconomic conditions. Breast milk production was evaluated using validated maternal-report indicators and categorized as adequate or inadequate. Data were analyzed using descriptive statistics and the Chi-square test, with statistical significance set at p < 0.05. Complete data were obtained from all 41 participants. Lactating mothers with adequate maternal nutritional status were more likely to report adequate breast milk production than those with inadequate nutritional status. The Chi-square analysis demonstrated a statistically significant association between maternal nutritional adequacy and breast milk production (p < 0.05). Maternal nutritional adequacy was significantly associated with adequate breast milk production among lactating mothers in a rural primary health care setting in North Aceh. These findings suggest that integrating routine nutritional assessment and nutrition-focused counseling into maternal and child health services may support favorable breastfeeding outcomes. Further longitudinal studies using objective measures of breast milk production are warranted to clarify the temporal relationship between maternal nutritional adequacy and breastfeeding outcomes.